In situ morphological characterization of hylocereus spp. (fam.: cactaceae) genotypes from antioquia and córdoba (colombia) / caracterización morfológica in situ de genotipos de hylocereus spp. (fam.: cactaceae) de antioquia y córdoba (colombia) (2013)
The genus Hylocereus includes many importantspecies for human and animal nutrition, including those known as dragon fruits. Although Colombia produces yellow pitaya on a commercial scale, there have been no advances for the red pitahaya crop. This study aimed to do an in situ evaluation of genetic material of wild red pitahaya (Hylocereus spp.) from three populations located in Antioquia and Córdoba; with special interest for the fruits, taking into account the desired characteristics by the market. To achieve this, 23 descriptors of stems and fruits, measurable in the field, were chosen; and 35 individuals where located, using GPS, and described. The populations were compared using mean comparison and the similarity was evaluated with cluster analysis. The stem descriptors differed in spine number, contour and margin hardness, areole distance and stem color; the first three are important for species distinction.According to the fruit descriptors, populations 1 and 2 presented similar fruits that were different from those of population 3, for almost all variables except total soluble solids content. The fruits of population 1 and 2 only differed for pulp weight. Individual 3 of population 1 presented fruits with the best characteristics for the market / El género Hylocereus presenta varias especies importantes en la alimentación humana y animal, incluyendo aquellas conocidas como pitayas rojas. Aunque Colombia produce comercialmente pitaya amarilla, no ha avanzado en el cultivo de pitaya roja. Este trabajo se propuso caracterizar in situ materiales genéticos silvestres de pitaya roja (Hylocereus spp.) provenientes de tres poblaciones de Antioquia y Córdoba, especialmente de sus frutos, según las características deseables para el mercado. Para ello,se eligieron 23 descriptores de tallos y frutos, medibles en campo; se ubicaron y georeferenciaron 35 individuos y se describieron. Las poblaciones fueron comparadas en cada uno de los descriptores usando una comparación de medias, además se evaluó la similitud entre poblaciones con un análisis de agrupamiento. Según los descriptores de tallos, hubo diferencias en: número de espinas, contorno y dureza de las márgenes, distancia entre areolas, altura yespesor de la arista, longitud y color del cladodio; las tres primeras características son importantes para diferenciar especies. Según los descriptores de fruto, las poblaciones 1 y 2 presentaron frutos más similares entre sí y diferentes de los de la población 3, en casi todas las variables excepto en el contenido de sólidos solubles totales. Los frutos de la población 1 y 2 sólo difirieron en el peso de la pulpa. El individuo 3 de la población 1 presentó frutos con mejorescaracterísticas para el mercado.